Assessing Critical Thinking Dispositions of Undergraduate Business Students in Nepal - Ojha, Gaurav (Journal of Business and Social Sciences Research, 2024)
This study examines the critical thinking dispositions of undergraduate students specializing in business and management studies at different university-affiliated colleges in Kathmandu Valley. The primary purpose of this study is to determine to what extent the sampled undergraduate students display critical thinking dispositions in a cross-sectional survey study related to management education in Nepal. The sample size of this study consists of 110 undergraduate students graduating in management and business specialisations, and the data was collected using the parameters of the California critical thinking dispositions inventory. The results of this study indicate a significant number of undergraduate students displayed negative, ambivalent, and insufficient critical thinking dispositions. This study reveals that critical thinking abilities of students are not fully developed during their undergraduate business and management studies. Therefore, this study suggests that academic institutions that offer management education need to create an institutional framework for critical thinking culture and offer academic environment that supports student’s development of critical thinking abilities.